Veselago lens and Klein collimator in disordered graphene. (7th February 2017) - Libisch, F; Hisch, T; Glattauer, R; Chizhova, L A; Burgdörfer, J
Abstract: We simulate electron transport through graphene nanoribbons of realistic size containing a p–n junction patterned by electrostatic gates. For a sharp p–n interface, Klein tunneling leads to refocusing of a divergent beam forming a Veselago lens. Wider transition regions allow only electrons with near-perpendicular incidence to pass the junction, forming a Klein collimator. Using a third nearest neighbor tight binding description we explore the influence of interface roughness and bulk disorder on guiding properties. We provide bounds on disorder amplitudes and p–n junction properties to be satisfied in order to experimentally observe the focusing effect and compare our predictions to very recent realizations.